Effect of milk and milk products consumption on physical growth and bone mineral density in Korean adolescents - Kim, Sun Hyo (The Korean Nutrition Society and the Korean Society of Community Nutrition, 2013)
This study was conducted to investigate the relationship among the current status of calcium intake from milk and milk products, physical growth and bone mineral density in 664 male and female middle school and high school students aged 15-17 years. In the study, the current status of calcium intake from milk and milk products was analyzed, and the height, body composition, and bone mineral density of the right heel bone (calcaneus) were measured. The daily calcium intake of milk and milk products was calculated as the 'dairy equivalent of calcium', which is the calcium content in 200 mL of white milk. The cutoffs of tertiles of the dairy equivalent of calcium were calculated and then the subjects were categorized into 3 groups according to the tertiles, Q1 group (lower intake group), Q2 group (middle intake group) and Q3 group (upper intake group). The daily calcium intake of milk and milk products in Q1, Q2 and Q3 groups was 16.2 mg, 99.7 mg, and 284.0 mg, respectively, and the ratio of milk and milk product consumption to the daily total calcium intake was 5.4%, 27.4%, and 49.7%, respectively. The ratio of total calcium intake to the daily recommended intake in study subjects was 30.5% in Q1, 42.3% in Q2, and 60.7% in Q3, with significant differences (P < 0.05). Height, body weight, BMI, and % of body fat in three tertile groups (Q1, Q2 and Q3) were not significantly different. However, the T scores for bone mineral density in female students in three tertile groups (Q1, Q2 and Q3) was significantly different (P < 0.05). The study showed that the intake of milk and milk products in adolescents, particularly in girls, can improve the bone mineral density without increasing body weight, and thus confirmed that milk intake is important in adolescence.